Acousto-optical modulation of light at a doubled sound frequency. (1st March 2016) - Kotov, V M; Averin, S V; Shkerdin, G N
Abstract: A method of acousto-optical (AO) Bragg diffraction is proposed that provides the amplitude modulation of optical radiation at a doubled acoustic frequency. The method is based on the double transmission of the light through the AO modulator made of a gyrotropic crystal and is experimentally tested by the example of the modulation of light with a wavelength of 0.63 μm, controlled by the paratellurite AO cell.